Challenges and Prospects of Shaping the Leading Positions of the Plekhanov Russian University of Economics in Training Students for Specialization ‘Management’ - M. N. Kulapov (Plekhanov Russian University of Economics, 2019)
The article provides results of the education and scientific center 'Management' work (OSCM), a new form of managing the profile chairs and interaction with faculties. The choice of this organizational form in the Russian Plekhanov University of Economics was correct, which is proved by May 2018 Decrees of the President of the Russian Federation. Shaping the leading positions of the university in training students for specialization 'Management' is ensured by integration and coordination of joint efforts of the OSCM managerial team, lecturers and employees of chairs, academic schools, research institutions and other structural divisions. Dynamics of the OSCM organizational structure shown by the authors is stipulated by focusing on resolving yearly program objectives of university development. Founding key chairs and research labs provides an opportunity to integrate the teaching process with the real practice of management, which is confirmed by international and professional-public accreditation of education programs. There are 20 key professional education programs of training bachelors and masters of management, 6 of them were accredited by the European Council on Business Education and 13 have professional- public accreditation. The demand for training programs for specialization 'Management' is provided by the whole set of measures, including system career advising of Moscow school leavers, partnership with the Regional Center of career advising and employment based in the Zemskiy gymnasia in Balashikha, the use of advanced education technologies and two-language programs, etc. The academic novelty of the article is connected with its critical comprehension of challenges and prospects of shaping leading positions in training students for specialization 'Management' on the basis of OSCM work analysis, studying the impact of current reforms on the university functioning. The authors put forward a number of recommendations dealing with the goal of attaining leading positions in training students for specialization 'Management'.